(3cJGH aj GdHjYs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3bGd GdeUfa(B: (3GdaUd GdKGfj; Cj ef aUhd cJGH GdHjY aj YbO GdHjY hGdEVGaI HjGfjI HfGA Ydi chf GdHjY gh GdYbO dG GdeSHH efg ef Gdfbd hGdGfJbGd Ch GddGejIs
(3BNQgG (B:s
(3BNQgG(B: (3hGdLedI HYO YOe JeGejI bGYOI GdGMJQGe aj faSg djS aj GdHjf EdG bGYOI GdEVQGQ hGdJYRjQ, hdbO YQaJ Cf djS JMJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis